Dubrovnik hospital in the First World War : Surgical procedures in the Dubrovnik hospital during the First World War as the foundation of the future surgical department - Car, Antun (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
Civilian hospitals in the Austro-Hungarian Monarchy continued to operate during the First World War, some converted into military hospitals, others as both military and civilian, and still others continued to treat only civilian patients. In Dubrovnik during the First World War, there were two military hospitals and the Dubrovnik city hospital, which remained civilian with a military part. As the war continued, the lack of doctors and medical personnel affected it more and more. The situation is worsened by lack of food and occasional epidemics of infectious diseases. In the hospital in Dubrovnik, demographic growth is slowing down due to the drop in births and a persistently high mortality rate. However, the hospital meets the requirements of Dubrovnik and its surroundings in the difficult wartime circumstances and follows advances in the surgical treatment of diseases. Surgical procedures during the First World War became the basis for the creation of the surgical department of the Dubrovnik hospital.
Keywords: First World War; surgical procedures; hospital departments; Dubrovnik Hospital